How often are antidepressants prescribed off‐label among older adults in Germany? A claims data analysis. Issue 4 (5th November 2020) - Schäfer, Wiebke; Reinders, Tammo; Riedel, Oliver; Haug, Ulrike
Abstract : Aim: To estimate the extent of off‐label prescribing of antidepressants in older adults and to characterize patients with off‐label vs on‐label prescriptions of antidepressants using a large German health claims database. Methods: Using data from the German Pharmacoepidemiological Research Database (GePaRD), we conducted a cross‐sectional study in adults aged 65 years or older with a dispensation of an antidepressant between 1 January 2009 and 31 December 2015 after a period of 365 days without such a dispensation. We assessed the overall and annual proportion of off‐label prescriptions of antidepressants by class and individual substance. Results: Among 263 276 incident users of antidepressants, the proportion of off‐label prescribing was 43.6% (95% CI 43.4‐43.8%) with little variation between 2009 and 2015 (42.2‐44.4%). The proportion of off‐label use was higher in men (49%) than women (41%). While the proportion of off‐label prescriptions was highest for tri‐ and tetracyclic antidepressants with 56.2% (amitriptyline 54.6%, maximum 65.9% for trimipramine), it amounted to 41.8% for selective serotonin reuptake inhibitors (citalopram 41.6%, maximum 46.0% for escitalopram) and was 51.2% for mirtazapine. Indicators of overall morbidity were similar in both groups, eg, pain was coded in 72% of off‐label users vs 77% of on‐label users (insomnia 20% vs 24%). Conclusion: Our study suggests a high prevalence of off‐label antidepressant use among older adults in Germany, which was not restricted to certain classes of antidepressants or individual antidepressants. Given the unclear risk‐benefit ratio, studies investigating the safety of off‐label use among older adults for individual antidepressants are urgently needed.